Research progress of Traditional Chinese Medicine nursing techniques for chronic obstructive pulmonary disease (慢性阻塞性肺疾病中医护理技术研究进展) - WANG Shuohan (王烁涵); HAN Lingyu (韩凌宇); ZHANG Li (张丽); DONG Mei (东梅) (中西医结合护理)
Chronic obstructive pulmonary disease (COPD) is a common and frequent disease of the respiratory system that threatens human health. Given the long treatment cycle, it is necessary to carry out effective nursing interventions to relieve clinical symptoms and improve quality of life during treatment. This paper briefly discussed the etiology and pathogenesis of COPD in Traditional Chinese Medicine, and summarized clinical application of Traditional Chinese Medicine nursing techniques for patients with COPD, in order to provide reference for clinical nursing practice. (慢性阻塞性肺疾病(COPD)是威胁人类健康的呼吸系统常见病、多发病。COPD治疗周期长, 科学有效的护理方法对改善患者临床症状、提升生活质量有着重要意义。本文主要是对COPD的中医病因病机加以阐述, 总结中医特色的护理技术在COPD中的应用现状, 以期为COPD患者的护理临床实践提供参考。)